BC-DIGIT: an interactive digital application / Noorsaidi Mahat … [et al.] - Mahat, Noorsaidi; Mohd Mustafa, Siti Nurul Ainun; Abdul Hamid, Siti Hamidah; Jasni, Mohd Dzuliqyan; Zulkifli, Mohd Zul Aswad (Faculty of Computer and Mathematical Sciences, 2022)
Covid-19 has changed most of the education teaching approaches around the world either synchronous or asynchronous approaches. This includes the Building Construction education for construction sites experiences and practices which are challenging for students. Nowadays, students can be very demanding because they have raised their learning criteria compared to the past generation. Therefore, new pedagogical paradigms need to emphasise creative thought. In this case, gamification in teaching and learning is a creative way to inspire students to learn by incorporating game features to achieve an enjoyable and exciting learning experience. Game-based learning incorporates new skills and concepts by voluntarily enhancing learning engagement and encouragement among players. Gamification is also a successful way to improve students' habits and attitudes towards learning. Here, Building Construction Digital Board Game (BC-DIGIT) is a digital board game project created for Building Construction education. The board game promotes knowledge and information creation, particularly for built environment students. this gamification project can help develop knowledge and information about Building Construction and improve essential skills for the construction industry’s students and future personnel.